Macroeconomic performance of the Israeli economy in the 21st millennium - Shachmurove, Yochanan; Zilberfarb, Ben-Zion (Economics and Business Review, 2020)
The Israeli economy in the first two decades of the 21st century is an exampleof an economic transformation that may serve as a role model for addressing manychallenges to economic growth. Data from this period have shown significant developmentsin economic growth over this relatively short period of time and indicate thatthese advances are attributable to policies targeting inflation, labor force participationand education. While challenges remain—including economic inequality, suboptimalhealth care and the threat of coronavirus pandemic to global growth—we explore developmentsevidenced to promote economic growth.